Effects of the Pore Size of Graphite on the Mechanical Properties and Permeability of a Porous Nozzle for Continuous Casting Process - Cho, Yong-Ho; Kim, Juyoung; Yoon, Sanghyeon; Lee, Heesoo (Korean Journal of Metals and Materials, 2011)
To analyze the effect of the pore size of graphite in a pore-forming agent, graphite was added to porous ceramics of Al_2O_3-SiO_2-ZrO_2 systems. The graphite had 45~75, 100~125, 150~180, and 75~180㎛dimensions. The properties of the ceramics, such as apparent porosity, density, dynamic elastic modulus,mechanical strength, and permeability, were investigated. The average pore size increased from 15.35㎛ to 22.32㎛ with the increase of the graphite size. The sample with the largest average pore size showed the highest mechanical strength and gas permeability. This was due to the sample with the largest pore size at the same porosity having fewer pores and larger distance between the pores than the sample with the smallest pore size, making cracks less likely to propagate. In addition, the large pore size reduced the repulsive power originating from the drag force between the gas and internal pore walls. KCI Citation Count: 1